A planarized B-phenyldibenzoborepin: impact of structural constraint on its electronic properties and Lewis acidity. Issue 41 (3rd May 2018) - Ando, Naoki; Kushida, Tomokatsu; Yamaguchi, Shigehiro
Abstract : Planarization of B -phenyldibenzo[ b, f ]borepin allows π-expansion across the B -phenyl group and makes this scaffold a useful electron-accepting unit for donor-π-acceptor type fluorophores. Abstract : A B -phenyldibenzo[ b, f ]borepin planarized with two methylene bridges was synthesized. The structural constraint on the B -phenyl group resulted in a bathochromic shift of the absorption and fluorescence properties as well as enhanced Lewis acidity. A donor–π–acceptor type derivative based on this scaffold exhibited intense fluorescence irrespective of the solvent polarity.